THE RIGHT TO EDUCATION AS AN INSTRUMENT TO THE RIGHTS OF CHILDREN AND ADOLESCENT PERSONALITY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The objective of the research is to demonstrate that the right to education is foreseen in the Federal Constitution as a fundamental and social right, as well as a right of instrument for the realization of the personality rights of children and adolescents. In hypothesis, education has the competence to control and help quality public management - with the objective of consolidating citizenship. Personality rights, like the development of personality, aim at the condition of the dignity of the human person. Within the problematic proposal, it was questioned which instrument allows promoting citizenship and human dignity for children and adolescents. In specific analysis, children and adolescents are vulnerable beings and are protected by comprehensive protection, the effects of not promoting education are irreversible, affecting the development of the individual causing social impacts. The methodology used consisted of bibliographic and documentary research on the topic.